Shadow economies and corruption all over the world: what do we really know? - Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2006)
Estimations of the size and development of the shadow economy for 145 countries, including developing, transition and highly developed OECD economies over the period 1999 to 2003 are presented. The average size of the shadow economy (as a percent of official GDP) in 2002/03 in 96 developing countries is 38.7%, in 25 transition countries 40.1%, in 21 OECD countries 16.3% and in 3 Communist countries 22.3%. An increased burden of taxation and social security contributions, combined with a labor market regulation are the driving forces of the shadow economy. Furthermore, the results show that the shadow economy reduces corruption in high income countries, but increases corruption in low income countries. Finally, the various estimation methods are discussed and critically evaluated
Keywords: 330; Schattenwirtschaft; Steuerbelastung; Steuermoral; Wirtschaftswachstum; Übergangswirtschaft; Schätzung; Welt; Entwicklungsländer; Osteuropa; OECD-Staaten